Parental interpretations of "childhood innocence": Implications for early sexuality education. Issue 6 (3rd October 2016) - McGinn, Laura; Stone, Nicole; Ingham, Roger; Bengry-Howell, Andrew
Abstract : Purpose: Despite general recognition of the benefits of talking openly about sexuality with children, parents encounter and/or create barriers to such communication. One of the key barriers is a desire to protect childhood innocence. The purpose of this paper is to explore parental interpretations of childhood innocence and the influence this has on their reported practices relating to sexuality-relevant communication with young children. Design/methodology/approach: In all, 110 UK parents and carers of children aged between four and seven years were involved in focus group discussions. The discussions were transcribed and thematic network analysis was subsequently applied to the data. Following the reading and re-reading of the transcripts for meaning, context and content, individual comments and statements were identified within the data set and grouped to generate themes. Findings: Childhood innocence was commonly equated with non-sexuality in children and sexual ignorance. Parents displayed ambiguity around the conceptualisation of non-innocence in children. Parents desire to prolong the state of childhood innocence led them to withhold certain sexual knowledge from their children; however, the majority also desired an open relationship whereby their child could approach them for information. Originality/value: UK parents have a strong desire to maintain the social construction of their children as inherently innocent. This discourse is affecting the way in which they communicate about sexually relevant information with their children.